2020
DOI: 10.1016/j.pec.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of first-person storytelling on changing health-related attitudes, knowledge, behaviors, and outcomes: A scoping review

Abstract: Objectives: First-person storytelling (FPS) has the potential to engage patients in changing behavior differently than didactic education. We assessed the prevalence of FPS in health education interventions; whether published FPS research has shown improvements in attitudinal, knowledge, behavioral, or clinical outcomes; and whether randomized controlled trials (RCTs) including FPS have shown more effectiveness than non-FPS interventions. Methods: A scoping review of FPS studies published before October 2019 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 66 publications
2
33
0
2
Order By: Relevance
“…Storytelling positively affected health-related outcomes by being therapeutic for the storyteller, eliminating barriers between physician and patient, and promoting health behavior change (DiFulvio et al, 2016 racial/ethnic minorities (Lipsey et al, 2020). The primary implication is that storytelling should be further utilized in public health and related fields like medical anthropology, with both fields recognizing the novelty it adds to research as a relatively new tool while acknowledging that more research is needed to fully demonstrate the benefits (Davidson & Falola, 2020;Kaplan-Myrth, 2007;Lipsey et al, 2020;Palacios et al, 2015). Finally, storytelling can provide new insight on current health issues, decrease researcher bias, and advance the quality of health care for patients and practitioners.…”
Section: What Were the Implications Of The Results?mentioning
confidence: 99%
See 2 more Smart Citations
“…Storytelling positively affected health-related outcomes by being therapeutic for the storyteller, eliminating barriers between physician and patient, and promoting health behavior change (DiFulvio et al, 2016 racial/ethnic minorities (Lipsey et al, 2020). The primary implication is that storytelling should be further utilized in public health and related fields like medical anthropology, with both fields recognizing the novelty it adds to research as a relatively new tool while acknowledging that more research is needed to fully demonstrate the benefits (Davidson & Falola, 2020;Kaplan-Myrth, 2007;Lipsey et al, 2020;Palacios et al, 2015). Finally, storytelling can provide new insight on current health issues, decrease researcher bias, and advance the quality of health care for patients and practitioners.…”
Section: What Were the Implications Of The Results?mentioning
confidence: 99%
“…The range of participants included parents, adolescents, young adults, seniors, essential service workers, survivors of traumatic experiences, health care professionals, and health care professional students. Variables included low-health literacy, high school education, ethnic minority status, low-socioeconomic status, aging population status, and English not as a first language (Kleinman & Benson, 2006; Lipsey et al, 2020; Roche et al, 2005; Stargatt et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stories may also be well-suited for educating patient populations, including Native Americans or First Nations people who have cultures steeped in oral traditions [ 67 - 70 ]. Finally, the digital storytelling library methodology can be applied to health areas outside of living donation, as first-person storytelling has been shown to improve health outcomes for patients who belong to racial or ethnic minorities, have low health literacy, and are of lower socioeconomic status [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…An online field experiment that explored the impact of shared illness narratives on the working lives of 166 people with chronic inflammatory bowel disease found that personal relevance enabled the reader to connect with the storyteller, increasing motivation and perceived ability to work [9]. These findings suggest that having platforms for people to communicate the experience of living with chronic pain may, in addition to providing a therapeutic intervention [8], may also improve public knowledge and awareness [10].…”
Section: Introductionmentioning
confidence: 99%